Can we measure the spiral and uterine artery blood flow by real‐time sonography and Doppler indices to predict spontaneous miscarriage in a normal‐risk population?. Issue 2 (May 2015) - Özkan, Mehmet Burak; Ozyazici, Elif; Emiroglu, Baris; Özkara, Enis
Abstract: Introduction : The predictive value of spiral artery flow Doppler measurements of a subsequent early miscarriage in first trimester pregnancy is explored here. Objective : The aim of this study is to determine uterine and spiral artery blood flow changes in first trimester subsequent miscarriages and correlate within the mechanisms of the Doppler indicies. Study design : The uterine artery and spiral artery pulsatility and resistance indexes, systolic and diastolic ratios, acceleration times, and blood flow of both the right and left uterine arteries were obtained by trans vaginal color Doppler ultrasonography in consecutive viable pregnancies between 5 and 12 gestational week. Women were subsequently classified as having continuing pregnancies or pregnancy loss before 20 weeks gestation. To predict subsequent pregnancy loss, Doppler findings were adjusted for maternal age, history of previous abortion, presence of subchorionic hematoma, embryonic bradycardia, and gestational age by means of multivariate logistic regression analysis. The cut‐off values are used for the ROC curve. Results : Twenty‐five pregnancies (11.7%) were spontaneously aborted before 20 weeks of gestational age. In 29 (13.6%) cases there were previously abortion history, 30 (14%) had bradycardia, and 37 (17.3%) had subchoronic hematoma. Regarding the parameters of uterine and spiral artery pulsatility and resistive index, acceleration time, systolic/diastolic ratios and blood flows, only uterine artery S/D low values were significantly associated with pregnancy loss in the multivariate logistic regression analysis (P = 0.0001, 95% CI: 4.968–55.675). Conclusion : The uterine artery systolic/diastolic ratios have a predictive value for early pregnancy loss and seem to be useful as a marker. On the other hand, spiral artery changes could be so local that they cannot be determined by the parameters of spectral Doppler techniques. This suggests that uterine vascular bed alterations should be measured to understand the prognosis of early pregnancy loss during the first trimester.